Treatment and Prognosis of Upper Tract Urothelial Cancer - Muhammad Asif, Safiullah, Muhammad Shahid Bhatti, Ghulam Mujtaba, Syed Muhammad Hassan Akhtar, Naveed Ahmed Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The uncommon tumor known as Upper Tract Urothelial Carcinoma (UTUC) can begin anywhere in the urinary tract, from the calyces of the kidneys to the openings of the ureter. Objective: Aim was to determine the effectiveness of treatment upper tract urothelial cancer among patients admitted to hospital. Methods: Total 30 patients of both genders were presented in this study. All the patients had upper tract urothelial cancer and admitted for treatment. 30 Patients received laparoscopic nephroureterectomy in group I and and 30 patients of group II received chemotherapy or radiation for treatment. Outcomes among both groups were compared. SPSS 24.0 was used to analyze all data. Results: Mean age of the patients in group I was 70.8 years and in group II mean age was 68.15 years. Majority of the patients were males among both groups. 17 cases of group I and 14 cases of group II had smoking history. We found group I had better outcomes as compared to group II but results were statistically insignificant. Recurrence rate in group II was 6 (20%) higher as compared to group I was 4 (13.3%). Conclusion: We concluded in this that both treatment was effective for UTUC carcinoma and had minimum recurrence rate. Keywords: UTUC, laparoscopic nephroureterectomy, Chemotherapy radiation, Recurrence